PERBANDINGAN MODEL PEMBELAJARAN STAD DENGAN MODEL TAI (TEAM ASSISTED INDIVIDUALIZATION) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Harsanti, Arni Gemilang (Profesi Pendidikan Dasar, 2017)
This study aims to determine the different of the application of Student Team Achievement Division models and Team Assisted Individualizaton models in mathematic  student achievement 0f class V SDN Gading 01 and SDN Kebonagung 02 in 2015/2016 school year. This research design uses quantitative research methods. Collecting data in this study uses test methods. Test methods in this study is post test given to the control group and eksperimental group. Data analysis is used t – test.The result of data analysis t – test obtained value = 5,26. At the significance level 5% with t table =1,701. So that is = 5,26 . Therefore  is rejected and  accepted. The conclusion of this study is that different between application of Student Team Achievement Division models and Team Assisted Individualizaton models in mathematic  student achievement 0f class V SDN Gading 01 and SDN Kebonagung 02 in 2015/2016 school year.